Optimizing SMEs Through Digital Design for Sustainable Industrial Development - Limano, Ferric (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
SMEs (Small and Medium Enterprises) are the pillars of Indonesia's economy, as evidenced by their significant contribution to the country's gross domestic product. The digital disruption era, particularly during the pandemic, has necessitated changes in product development and marketing strategies for SMEs, pushing them towards digital approaches. This research aims to study the application of digital design in branding and digital marketing strategies by SMEs, providing recommendations based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The qualitative research method utilized data from two product samples: Maicih (Food) and Compass (Fashion). In the case of Maicih, engagement was built through a viral snack brand known for its unique spicy flavors, enjoyed socially. The brand's social media, featuring the tagline "cerita emak" (mother's stories), helped foster interaction and drive traffic to online marketplaces. For Compass, the focus was on building a sneaker community, facilitating buying and selling within the community, and fostering emotional connections through collaborations. This study encompasses market analysis, brand design, and the digital development and implementation process. SMEs that can adapt and sustain themselves can address the sustainability goal: "Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation.â€